Evolution of genome fragility enables microbial division of labor. Issue 3 (2nd February 2023) - Colizzi, Enrico Sandro; van Dijk, Bram; Merks, Roeland M H; Rozen, Daniel E; Vroomans, Renske M A
Abstract: Division of labor can evolve when social groups benefit from the functional specialization of its members. Recently, a novel means of coordinating the division of labor was found in the antibiotic‐producing bacterium Streptomyces coelicolor, where specialized cells are generated through large‐scale genomic re‐organization. We investigate how the evolution of a genome architecture enables such mutation‐driven division of labor, using a multiscale computational model of bacterial evolution. In this model, bacterial behavior—antibiotic production or replication—is determined by the structure and composition of their genome, which encodes antibiotics, growth‐promoting genes, and fragile genomic loci that can induce chromosomal deletions. We find that a genomic organization evolves, which partitions growth‐promoting genes and antibiotic‐coding genes into distinct parts of the genome, separated by fragile genomic loci. Mutations caused by these fragile sites mostly delete growth‐promoting genes, generating sterile, and antibiotic‐producing mutants from weakly‐producing progenitors, in agreement with experimental observations. This division of labor enhances the competition between colonies by promoting antibiotic diversity. These results show that genomic organization can co‐evolve with genomic instabilities to enable reproductive division of labor. Synopsis: A computational model of the multicellular bacteria Streptomyces reveals that if antibiotic production trades off with replication, genome architecture can evolve to support a mutation‐driven division of labor. In silico bacterial colonies divide labor between replication and antibiotic production by evolving a genome architecture that physically segregates genes for these different functions and allows them to be dissociated due to mutations at fragile sites. Division of labor is driven by mutations and is reminiscent of the division between germ and soma in multicellular eukaryotes: One class of cells specializes in reproduction, while the other class, comprising the mutants, focuses on costly antibiotic production. In this system, which replicates dynamics observed in S. coelicolor, mutant cells effectively function as soma by enhancing colony fitness, despite being sterile. Abstract : A computational model of the multicellular bacteria Streptomyces reveals that if antibiotic production trades off with replication, genome architecture can evolve to support a mutation‐driven division of labor.